Peran Pemerintah Dalam Menghadapi Tantangan Demokrasi Akibat Diskriminasi Ekonomi: Studi Kasus Hak Kesempatan Kerja Di Papua - Argoebie, Bella; Sizdah, Raisha; Kurniawan, Syahwa Fitria; Azis, Ardhana Ulfa (JURNAL LANSKAP POLITIK, 2025)
The right to employment in Papua is still a crucial issue that is included in the challenges of democracy in Indonesia. It is evident from the 6.48% open unemployment rate that is still high in Papua because indigenous Papuans feel the inequality of access they get compared to immigrant groups. The problem studied is how the government's role in facing democratic challenges arising from economic discrimination, especially related to the right to employment opportunities in Papua. This research identifies the specific role of the government in reducing unequal access to employment and the impacts of this problem on democratic stability and explores how this economic injustice affects the principle of inclusiveness in Indonesian democracy. The researcher used a qualitative method approach that drew data sources from books, journals, previous research, and data from various websites on the internet. The research process involves systematic data collection techniques through observation and analysis of documents or archives related to the research subject, such as records of reports, books, or official documents. Based on the results of the discussion, it can be concluded that the central and regional governments have made many efforts to provide solutions to the problem of solving the challenges to democracy that occur in Papua. This is evidenced by the discovery of various special policies made by the central government for Papua such as the special autonomy policy, affirmation quota, scholarships to the Papua youth creative hub program. The author hopes that this research is useful for reference or foundation and supports further research and can be useful for the advancement of political science. Keywords: Economic Discrimination, Democracy, Papua. Abstrak Hak kesempatan kerja di Papua masih menjadi permasalahan krusial yang termasuk ke dalam tantangan demokrasi di Indonesia. Terbukti dari angka 6,48% tingkat pengangguran terbuka yang masih tinggi di Papua disebabkan oleh orang asli Papua merasakan ketimpangan akses yang mereka dapatkan dibandingkan dengan kelompok pendatang. Permasalahan yang diteliti adalah bagaimana peran pemerintah menghadapi tantangan demokrasi yang timbul akibat diskriminasi ekonomi, khususnya terkait hak kesempatan kerja di Papua. Penelitian ini mengidentifikasi peran spesifik pemerintah dalam mengurangi ketimpangan akses kerja serta dampak-dampak masalah ini pada kestabilan demokrasi serta mengeksplorasi bagaimana ketidakadilan ekonomi ini memengaruhi prinsip inklusivitas dalam demokrasi di Indonesia. Peneliti menggunakan pendekatan metode kualitatif yang mengambil sumber data dari buku, jurnal, penelitian terdahulu, dan data-data dari berbagai situs web di internet. Proses penelitian melibatkan teknik pengumpulan data secara sistematis melalui observasi serta analisis dokumen atau arsip yang berhubungan dengan subjek penelitian, seperti catatan laporan, buku, atau dokumen-dokumen resmi. Berdasarkan hasil pembahasan dapat disimpulkan bahwa pemerintah pusat maupun daerah banyak banyak melakukan segala upaya untuk memberi solusi atas penyelesaian masalah tantangan demokrasi yang terjadi di Papua. Hal ini dibuktikan dari ditemukannnya berbagai kebijakan khusus yang dibuat pemerintah pusat untuk Papua seperti kebijakan otonomi khusus, kuota afirmasi, beasiswa hingga adanya program Papua youth creative hub. Penulis berharap penelitian ini bermanfaat untuk acuan atau landasan serta mendukung penelitian selanjutnya dan dapat berguna untuk kemajuan ilmu politik. Kata kunci : Diskriminasi Ekonomi, Demokrasi, Papua.